2015
DOI: 10.1039/c5ra02835c
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-based systems for carbon dioxide capture, storage and recycling: from leaves to synthetic nanostructured materials

Abstract: Magnesium is used as leitmotif in this review in order to explore the systems involved in natural and artificial CO2 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
87
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 300 publications
(887 reference statements)
6
87
0
Order By: Relevance
“…Infrared spectroscopy and volumetric data suggested that the main interaction between CO 2 and UTSA-16 was due to the direct interaction of CO 2 with K + ions. This result is in line with what was reported in the case of a study that describes the interaction of CO 2 with K + open metal sites in K-ZSM-5. 19 Moreover, CO 2 isosteric heat of adsorption evaluated in this work and the one obtained by Zukal et al 23 in the case of CO 2 interacting with the K-MCM-22 zeolite are very similar (39.7 vs. 41.1 kJ mol À1 at zero-coverage).…”
Section: Discussionsupporting
confidence: 92%
“…Infrared spectroscopy and volumetric data suggested that the main interaction between CO 2 and UTSA-16 was due to the direct interaction of CO 2 with K + ions. This result is in line with what was reported in the case of a study that describes the interaction of CO 2 with K + open metal sites in K-ZSM-5. 19 Moreover, CO 2 isosteric heat of adsorption evaluated in this work and the one obtained by Zukal et al 23 in the case of CO 2 interacting with the K-MCM-22 zeolite are very similar (39.7 vs. 41.1 kJ mol À1 at zero-coverage).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, their removal from air or effective capture at the point source will continue to be an area of intense study. Likewise, separation of CO 2 is also critical in the processing of natural, shale or bio gas for usage in energy and transportation [4][5][6][7]. The presence of CO 2 not only reduces the energy content of natural gas, it induces severe corrosion of equipment and pipelines [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to applications, a strong obstacle is represented by their well-earned reputation as air and moisture sensitive materials. [6][7][8][9] The iconic and most famous MOF, MOF-5, decomposes after exposure to air for less than 10 min. 8,10 Several MOFs have been reported since then, 7,11,12 which have moisture stabilities going from fair (HKUST-1) 13 to exceptional (e.g.…”
mentioning
confidence: 99%
“…Besides a few exceptions, 19 MOFs based on s-block metals are characterized by very poor air stability. 6 This is related to the higher ionic character of the metal-ligand bonds, with respect to those based on transition metal cations, 9 making them more reactive towards atmospheric water. Nevertheless, the high abundance on Earth of some of these elements makes them more affordable from an economic point of view, and allows widespread application of these MOFs, with respect to those based on transition metal elements.…”
mentioning
confidence: 99%
See 1 more Smart Citation